Comparison between Islamic and Conventional Banking: Evidence from Malaysia - Abduallah, Al-Mamun; Qaiser Rafique, Yasser; Harry, Entebang; Md. Ashikur, Rahman; Thurai Murugam, Nathan; Shazali, Abu Mansor (American Research Institute for Policy Development, 2014)
Purpose: To determine the financial performance of Islamic banks and non-Islamic banks from 2003 to 2010 in Malaysia by applying the theory of Sharī’ah Conformity and Profitability model. Methodology: This study used accounting ratios which included profitability ratio, liquidity ratio and credit risk ratio to measure the financial performance of the Malaysian banks. Findings: Results indicate that conventional banks perform better in profitability, while Islamic banks perform better in liquidity and credit risk. In t-test of the return on asset (ROA) and total equity to net loans, there are no major difference between Islamic banks and non-Islamic banks. In the return on equity and common equity to total assets, there are statistically significant differences in these two groups. The statistically significant difference was shown in the area of liquidity which means that the Islamic banks liquidity performance has major difference with the non-Islamic banks. These finding are partially rejecting null hypothesis of profitability ratio and credit risk ratio. Moreover, the results are also rejecting null hypothesis of liquidity ratio, that there is statistically significant difference in the mean of liquidity ratio between Islamic banks and non-Islamic banks.